Mediation Of Transfer Motivation On The Relationship Between Supervisor Support, Peer Support And Transfer Of Training - Wasilu Suleiman; Mudiyanselage Saman Dassanayake; Abang Ekhsan Abang Othman (International Journal of Business and Society, 2017)
This paper investigated the mediation role of transfer motivation on supervisor and peers’ support in transferring training on the population of teachers. The constantly changing attitude of employees towards job has negatively affected the traditional employment engagement that offers an employee a sense of social support from supervisors and peers in their jobs. Thus, the emergence of additional several new training transfer variables from the studied data indicates that the existing training transfer models can be modified further. Hence, the hypotheses of this study are formulated.Survey design method and simple random sampling techniquewere utilized. Additionally, data is collected through survey questionnaire on the basis of 5-points Likert scale.An aggregate of 605 copies of the questionnaire were finally retained for analysis. Smart-PLS measurement and structural model were the procedures employed to assess and evaluate the statistical significance of relevant path coefficients. The findings showed that the extent to which employees are provided with social support in their jobs would drive them to be desirous in making persistent and intense efforts towards utilizing skills and knowledge learned in the work settings. Also, this study highlighted that transfer motivation is a key element in the transfer of training processes.